The Testimony of Moses in the Fourth Gospel: Beyond the Passover Feast, and into the Wilderness - Page, S.J., James (Lumen et Vita, 2021)
By examining the narrative framing of the Eucharistic Discourse (Jn 6:25-71) around the ancestral journey through the wilderness as recorded in Numbers, this paper highlights the intimate connection that the Fourth Gospel has to its Jewish context. In the Fourth Gospel’s Eucharistic Discourse, Jesus is not framed by the Passover Lamb, which the people offer to propitiate the Divine, but as manna from heaven, a gift from the Divine to the people, brining Life into the world. In the spirit of Nostra aetate, I conclude with some proposals for future interreligious dialogues that could fruitfully take place within these new parameters.